Stakeholders collaboration management of Rinjani Lombok UNESCO Global Geopark: social capital perspectives - Octavianti, Meria; Suryana, Asep; Bajari, Atwar; Ismail, Nurzali (Universitas Padjadjaran, 2023)
Background: The Executive Board of RLUGGp Management Agency, officially, is the designated technical organizer for Lombok Rinjani Geopark, established by the Governor of West Nusa Tenggara. However, in reality, it needs more authority to manage the Lombok Rinjani Geopark area. The Executive Board of RLUGGp Management office can only fulfill its functions with jurisdictional control over regional management. Purpose: This research aims to investigate the forms of collaboration among the actors involved in managing Geopark Rinjani Lombok. Methods: It is a qualitative and explorative case study, with data collection through In-depth interviews, participatory observations, and document analysis. Results: Stakeholder classification according to geopark management: (1) stakeholders based on their connection to the areas within the delineation of Geopark Rinjani Lombok; (2) stakeholders based on their hierarchical position within the government structure; (3) stakeholders who are part of the internal staffs of Geopark Rinjani Lombok Management Board; and (4) stakeholders supporting the management of Geopark Rinjani Lombok. The voluntary formation of interpersonal connections and the cultivation of trust among stakeholders, who are social actors within a social system, serve as the foundation for collaboration, coordination, and communication. Conclusion: Communities are pivotal in the successful execution of diverse development programs within Rinjani Lombok Geopark. Additionally, the Rinjani Geopark Youth Forum (RGYF) serves as the most substantial additional force in the execution of all programs. Implications: The dissatisfaction of each actor will hinder the achievement of the program objectives. Effective managerial communication should be practiced by a leader with authority and a significant role in the management of Geopark Rinjani Lombok.